Composition and formation conditions of the Upper Riphean terrigenous rocks (Dzhezhimparma Uplift, Southern Timan) - N. Yu. Nikulova (Известия высших учебных заведений: Геология и разведка, 2017)
The results of the study of the composition of the Upper Riphean terrigenous rocks of Dzhezhimparma Uplift at Southern Timan have been presented. On the basis of the lithological, geochemical and mineralogical data, the sedimentary material has been determined to be accumulated in the shore-marine extremely shallow-water conditions of a passive continental margin. The formation of the composition of the rocks involved the eroding products of the metamorphites of the ancient continent and slightly altered in a cold climate acid magmatic rocks. The postsedimentation transformations of the Upper Riphean rocks correspond to the stage of the late diagenesis-initial catagenesis.